Study of Animal-Based Food Product Labeling use - Candra Pungki Wibowo; Suci Paramitasari Syahlani; Sudi Nurtini (Buletin Peternakan, 2019)
This study was conducted to identify the food labeling profile in animal-based food products based on consumers’ age and gender, consumers’ preference of the information provided in the label, consumers’ behavior in reading the label, and consumers’ knowledge about food labeling. A total of 100 respondents participated in the study. The sampling was done by using judgmental sampling method with the following criteria: (1) respondent has bought animal-based food products within the last month of the study; (2) respondent’s age was over 18 years old. The data were analyzed descriptively and by using regression analysis. The results showed that female respondents and a group of 50 years or older respondents were used to read the food label frequently compared to other respondent groups. The type of information which considered as the most important was the expiration date, followed by product’s name, ingredients, halal status, nutritional value, product’s instruction for usage and its irregularities, net weight, and the producer’s name and address. This study also identified that the majority of the respondents, as many as 67%, already had good knowledge about food labels, while the other 32% had adequate knowledge, and only 1% of the respondents had a little knowledge about food labels. It can be concluded that consumers’ perception of the potential risks on animal-based food products affect their behaviour in reading the label (p<0.05) while consumers’ health condition and time availability to buy the products did not affect their behaviour in reading the label in animal based food products.